Nursing of a neonate with multiple organ dysfunction syndrome treated by blood purification (血液净化治疗新生儿多器官功能障碍1例的护理体会) - LIN Dongying (林东莹); QING Qing (青青); WANG Yiming (王一鸣); QI Lingling (漆玲玲); WANG Yan (王燕) (中西医结合护理, 2022)
This paper summarized the experience of nursing measures for a neonate with multiple organ dysfunction syndrome treated by continuous blood purification. Key issues of nursing included central venous catheter insertion and maintenance, strict monitoring of vital signs, regular testing of internal environment of the body, monitoring of indexes of blood filter, prevention of hypothermia, hypotension, hemorrhage and blood coagulation, strengthening the sedation and analgesia, and airway management. (本文总结血液净化治疗1例新生儿多器官功能障碍的护理经验, 包括中心静脉导管置管及维护, 严格记录生命体征, 定期检测内环境, 密切监测血滤机各压力值、血流速, 积极预防低体温、低血压、出血及凝血等并发症, 镇静镇痛及管道护理等。)